2001
DOI: 10.2166/wst.2001.0728
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of solar radiation and solar heating to disinfect drinking water sources

Abstract: Waterborne diseases are still common in developing countries as drinking water sources are contaminated and feasible means to reliably treat and disinfect these waters are not available. Many of these developing countries are in the tropical regions of the world where sunlight is plentiful. The objective of this study was to evaluate the effectiveness of combining solar radiation and solar heating to disinfect contaminated water using a modified Family Sol*Saver System (FSP). The non-UV transmittable cover she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…The inactivation of select bacteria, viruses, and protozoa due to UV-A radiation and heat has been studied extensively in studies under both simulated and natural conditions (Berney et al 2006;Boyle et al 2008;Dejung et al 2007;Heaselgrave et al 2006;Joyce et al 1996;Méndez-Hermida 2007;McGuigan et al 1998;Rijal & Fujioka 2001). It has been shown that a synergistic effect in low-turbidity water is observed when water temperature exceeds 45 o C, at which point the combined inactivation effectiveness is greater than the individual contributions of radiation and heat (McGuigan et al 1998).…”
Section: Solar Water Disinfectionmentioning
confidence: 99%
“…The inactivation of select bacteria, viruses, and protozoa due to UV-A radiation and heat has been studied extensively in studies under both simulated and natural conditions (Berney et al 2006;Boyle et al 2008;Dejung et al 2007;Heaselgrave et al 2006;Joyce et al 1996;Méndez-Hermida 2007;McGuigan et al 1998;Rijal & Fujioka 2001). It has been shown that a synergistic effect in low-turbidity water is observed when water temperature exceeds 45 o C, at which point the combined inactivation effectiveness is greater than the individual contributions of radiation and heat (McGuigan et al 1998).…”
Section: Solar Water Disinfectionmentioning
confidence: 99%
“…E. coli can be reduced by 3 logs with pasteurization at 65 o C within 3 hours. The same reductions can be achieved in a combination of solar disinfection and pasteurization within 2 hours at 56°C [37].…”
Section: Heatingmentioning
confidence: 67%
“…This necessity was made evident by the results found by Rijal and Fujioka (2001), who demonstrate that a disinfection system based on the synergistic effect of solar radiation and temperature, for the purpose of disinfecting drinking water, suffered reduced efficiency on cloudy days. Further, the factors mentioned by Balladin et al (1999) and Hanson et al (2004) as having influenced the microbiological quality of treated water in their studies highlight the need for adequate operation and maintenance of the equipment in order to avoid any future failures.…”
Section: Total Coliform and Escherichia Coli Removal Efficiencymentioning
confidence: 99%